P07.25 Comparison of cobas® hsv 1/2 test, quidel lyra™ direct hsv 1+2/vzv, bd probetectm hsv 1/2 qx assay and sanger sequencing using clinician-collected anogenital lesion swabs. (13th September 2015) - Young, S; Van Der Pol, B; Taylor, S; Fife, K; Hook, E; Patel, R; Ding, K; Hemyari, P; Duncan, J; Tang, S; Liesenfeld, O; Osiecki, J; et al.
Abstract : Objectives: The objective of this study was to evaluate the cobas ® HSV 1 and HSV 2 Test using clinician-collected swab specimens from external anogenital lesions as part of a large multicenter clinical trial. Methods: Two swabs were collected from patients with possible HSV infection at 8 geographically diverse sites. The first swab was used for the Quidel Lyra™ Direct HSV 1+2/VZV on the Cepheid SmartCycler II System and the second for the cobas ® HSV 1 and 2 Test. The Quidel Lyra™ Direct HSV 1+2/VZV test was performed at a reference laboratory and the cobas ® HSV 1 and HSV 2 Test was performed at 3 sites. Discrepant analysis included HSV culture using the ELVIS ® HSV ID and D³ Typing Test, a second FDA-cleared nucleic acid amplification test (BD ProbeTec TM Herpes Simplex viruses [HSV 1 and 2] Q x Amplified DNA Assays) and Sanger sequencing. The sensitivity and specificity were calculated by comparing cobas ® HSV 1 and HSV 2 Test results with the Quidel Lyra™ Direct HSV 1+2/VZV test following discrepant analysis using the majority result from the three comparator tests. Results: There were 229 HSV positive subjects, with 73 HSV-1 (44 female, 29 male) and 157 HSV-2 (78 female, 79 male) positive subjects, among 409 evaluable participants (205 female, 204 male). The sensitivity and specificity of the cobas ® HSV 1 and HSV 2 Test compared to the Quidel Lyra™ Direct HSV 1+2/VZV following discrepant analysis for HSV-1 was 98.6% (72/73) and 97.0% (326/336), respectively, and for HSV-2 was 100% (157/157) and 92.9% (234/252), respectively. Conclusion: The cobas ® HSV 1 and 2 Test, on the automated cobas ® 4800 system, displayed excellent performance compared Quidel Lyra™ Direct HSV 1+2/VZV Test combined with discrepant analysis. The test is highly suitable to detect HSV in clinician-collected anogenital swab specimens from patients with suspected HSV infection. Disclosure of interest: This clinical trial study was supported by Roche Molecular Diagnostics.